DOMINASI SKEMA BISNIS DALAM OSS RBA SEBAGAI ANCAMAN BAGI MASA DEPAN PERTANIAN DAN TATA GUNA LAHAN DI INDONESIA - Veronica Kinanthi Sihutami (LPPM institut Teknologi Bisnis AAS Indonesia, 2025)
The dominance of business interests in the risk-based business licensing (OSS RBA) policy has created a new dynamic in the relationship between business law and agrarian law in Indonesia. The OSS RBA system, implemented through Government Regulation No. 5 of 2021 under the umbrella of the Job Creation Law, was designed to simplify bureaucracy and attract investment. However, in practice, this scheme has opened up ample space for corporations to access and control land, including productive agricultural land, without robust land-use control mechanisms. The conversion of agricultural land to industrial areas, housing, and other commercial projects has been massive and rapid, leading to the degradation of agrarian space, unequal access to land, and threatening national food security. This study aims to critically evaluate how the dominance of business logic in the OSS RBA has displaced the principles of agrarian justice and environmental sustainability that should be maintained within the national land law system. Using a normative-juridical approach and qualitative analysis, this study recommends the need to reformulate business licensing policies to be more sensitive to the social function of land and the importance of integrating agrarian values into the business legal framework. Without a shift in the legal paradigm that prioritizes sustainability and spatial equity, the future of agriculture in Indonesia will be increasingly marginalized by the logic of capital accumulation and economic expansion alone. Keywords: OSS RBA, Land Conversion, Investment, Licensing, and Food Security.